Antimicrobial activities of isoprene compounds produced by an endophytic fungus isolated from the leaves of Coleus amboinicus Lour. - Puji Astuti; Rollando Rollando; Subagus Wahyuono; Arief Nurrochmad (GarVal Editorial Ltda., 2020)
Context: Medicinal plants have been reported to produce various bioactive molecules. In this study an endophytic fungus was isolated from the leaves of Coleus amboinicus Lour., a medicinal plant used in Jamu and the fungus was identified as Athelia rolfsii. Aims: To isolate, identify and characterize bioactive compound present in ethyl acetate extract of fermentation broth and determine its antimicrobial activities. Methods: The compound was isolated and purified by Preparative Thin Layer Chromatography. Antimicrobial activities were conducted by determining its IC50 and MBC (Minimum Bactericidal Concentration) values against Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis, Salmonella typhi and Staphylococcus mutans. The structure of the bioactive compound was deduced by spectroscopic data. Results: The bioactive compound displayed antimicrobial activities with IC50 of 0.86, 1.35, 1.33, 2.69, 1.9, 0.24 µg/mL and MBC values of 40, 40, 40, 40, 20, 20 µg/mL against S. aureus, E. coli, P. aeruginosa, B. subtilis, S. typhi, S. mutans, respectively. Based on IR, LC-MS, 13C-NMR, 1H-NMR data, the bioactive compound was suggested to consist of two compounds, methyl hemiterpenoate as a major compound and methyl, 2,3 diene-butanoate as the minor one. Conclusions: The endophytic fungus isolated from the leaves of C. amboinicus produced antimicrobial agents which could be potential for further development.